APLIKASI DUA MACAM KOMPOS LIMBAH PERTANIAN TERHADAP PERTUMBUHAN DAN SERAPAN KALIUM TANAMAN JAGUNG (Zea mays L.) - yenni dwi ismawati (AGRONISMA, 2020)
This study aims to determine the growht and uptake of potassium nutrient due to the provision of two kinds of compost from agricultural waste at different doses. The design used Factorial Randomized Block Design (RAK) with control. The first factor was the kinds of compost (P1= Peanut stack and P2= Sugar cane leaf litter) and the second factor was the application dose (D1= 5 ton.ha-1, D2= 10 ton.ha-1, D3= 15 ton.ha-1 dan D4= 20 ton.ha-1) and control. The results showed that giving two kinds of compost form agricultural waste with different dose did not have a significant effect on growth but showed a significant effect on total potassium uptake and optimum dose at total potassium uptake is P1 12,46 ton.ha-1 and P2 10,73 ton.ha-1.